Effiziente Geometrierekonstruktion nach Topologieoptimierung eines Motorhalters - Mayer, Johannes; Sippl, Christian; Hufnagel, Thomas; Wartzack, Sandro (Konstruktion, 2024)
Topology optimization (TO) can be the starting point for efficient material use and high-performance lightweight components. However, a reconstruction of the geometry in a separate process step is necessary after TO. Especially if the optimization result is not considered in the development process as an abstract surface model but as parametric computer-aided design (CAD) geometry, the reconstruction is laborand time-intensive. In contrast, this article discusses the application of a new feature-based research method to an engine bracket from MAN. Instead of elaborate design cycles, the method supports automation and parametrics.
CRIS-Team Scopus Importer:2024-11-22